Exposure to the real ambient air pollutants alters the composition of nasal mucosa bacteria in the rat model. (January 2022) - Yan, Tenglong; Wang, Weiwei; Xia, Jiao; Jia, Jiaxin; Xu, Jiayu; Dan, Mo; Zhou, Shupei; Niu, Piye; Gong, Shusheng; Chen, Zhangjian; Bai, Yi; Chen, Tian; et al.
Abstract: Studies have indicated that ambient pollutant exposure correlates with nasal disease, in which nasal mucosa microbiota play a crucial role. However, the association between exposure to real-ambient air pollutants and the composition of nasal mucosa microbiota has not been well studied. This study aimed to explore the composition of nasal mucosa microbiota after exposure to real-ambient air pollutants with a special system. We monitored PM2.5, O3, etc. in the system and confirmed PM2.5 and O3 were the main pollutants. SD rats were exposed to the system for 16 weeks in summer or 22 weeks in autumn-winter. The concentrations of PM2.5 were 24.00 μg/m 3 in the Summer stage and 22.21 μg/m 3 in the autumn-winter stage. The O3 concentrations were 25.46 and 13.55 μg/m 3, respectively. Exposure altered bacterial beta diversity in the summer stage. There were 4 and 3 different bacteria at the king, order, family and genus levels between the two groups at the two stages, respectively. The abundance of opportunistic pathogens changed, Pseudomonas decreased in summer stage, and Bifidobacterium increased in the autumn-winter stage. The influence of the season on the nasal mucosa microbiota was analyzed. The alpha diversity of the autumn-winter stage was higher than that of the summer stage. LEfSe analysis revealed 34 differential bacterial taxa at the king, order, family and genus level in the two control groups and 31 of the two exposure groups, which were not the same as the bacteria between the control groups and exposure groups. We found that PM2.5 combined with O3 exposure was associated with the composition of the nasal mucosa microbiota and the abundance of opportunistic pathogens, in which season likely impacted the microbiota. Graphical abstract: Image 1 Highlights: PM2.5 jointed O3 exposure caused alternation of beta diversity of nasal mucosa microbiota. PM2.5 jointed O3 exposure can alter the composition of nasal mucosa tissues and opportunistic pathogen. Season was also a crucial factor to affect the nasal bacterial.